Debating the East Asian peace what it is, how it came about, will it last? - Bjarnegard, Elin; Kreutz, Joakim (NIAS studies in Asian topics, 2017)
East Asia (including Southeast Asia) used to be the world's deadliest battleground but since the 1980s there has been a sudden and marked reduction in battle deaths. This phenomenon, which has become known as the East Asian Peace, has spurred much debate. This volume reflects on some of the most prominent of these debates.